Quantificação das raízes finas em um povoamento de Pinus taeda L., na região dos Campos de Cima da Serra, RS - Lopes, Vicente Guilherme (2009)
This study was conducted at Campos de Cima da Serra physiographic region, Cambará do Sul, RS, Brazil. The objectives of these study were: to comparatively quantify, the length and the biomass of fine roots (≤ 2,0 mm) inside the soil and in the litter and relate comparatively, soil chemical and physical variables in a Pinus taeda L., with 15 years of age, stand, implanted in a 3 x 2 m spacing, in 1993 and in a native grass area close to it. Samples were obtained through the use of monoliths methods described by Böhm (1979), based on the digging 3 monoliths (25 cm x 25 cm x 40 cm each), distributed inside the stand and 3 in native grass area. Roots were separated from the soil through washing and catching; after they were distributed over a white sheet of paper, where with a digital camera supported by a support with fixed height, 2.045 images were obtained. With the aid of the software, the images were processed to quantify roots length. After this procedure, the roots were dried in an oven and then weighed for biomass determination. Fine roots total length in Pinus stand, in 40 cm soil profile, including litter layer, was 68413 km ha-1, where the most part of them was concentrated in the first 20 cm and in the litter. In native grass area, the total length in 40 cm soil profile, was 173550 km ha-1, 42,82% (74313 km ha-1) of the total length is concentrated in the layer 0 10 cm. The roots density in native grass is 234, 28% higher than in Pinus. In Pinus until 40 cm depth, 3,52 Mg ha-1 was counted for fine roots biomass. Native grass showed 5,628 Mg ha-1, almost twice of fine roots biomass in Pinus. In both areas, soil chemical conditions, showed correlation with roots length and biomass. In Pinus, the main factors were P>K>V>Mg>Ca, on the other hand, in native grass area, the main factors were P>K>Ca>Mg>V. The great presence of fine roots in Pinus litter is important for cycling process, nutrients and water availability. After forest harvesting, litter and residues layer should remain, aiming the maintenance of soil productive potential.